Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3997/1873-0604.2011005
|View full text |Cite
|
Sign up to set email alerts
|

3D magnetic interpretation of the Regis kimberlite pipe, Minas Gerais, Brazil

Abstract: In the present work, high-resolution ground magnetic data are used to unveil the structure of the Regis kimberlite pipe, which is located in a well-known diamondiferous province in the central portion of Brazil. The main tectonic feature of the area is a NW-SE major crustal fracture zone, extending for more than 3000 km within Brazil, along which Regis and several other kimberlite pipes have intruded. The area is located at low magnetic latitude (inclination approximately 27 o south) and the ground magnetic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
2
0
3
Order By: Relevance
“…The Regis kimberlite is located in the central portion of the APIP, and it intruded along the so-called 125-AZ lineament, a major NW-SE crustal zone extending over 3000 km within the Brazilian territory (Menezes and La Terra, 2011). The pipe intruded into plane layers of inter-bedded red quartzites and green schists of the São Francisco Supergroup (Castro and Dardenne, 2000).…”
Section: Geological Settingmentioning
confidence: 98%
“…The Regis kimberlite is located in the central portion of the APIP, and it intruded along the so-called 125-AZ lineament, a major NW-SE crustal zone extending over 3000 km within the Brazilian territory (Menezes and La Terra, 2011). The pipe intruded into plane layers of inter-bedded red quartzites and green schists of the São Francisco Supergroup (Castro and Dardenne, 2000).…”
Section: Geological Settingmentioning
confidence: 98%
“…Estes valores são associados ao kimberlito alterado no centro (em azul) e nos tons de verde e amarelo, a rocha encaixante, indicando que a densidade do kimberlito alterado é menor que o filito, rocha encaixante. Este contraste pode ser observado visto que a densidade do kimberlito alterado (menores profundidades), é em média 2.4 g/cm 3 enquanto que do filito, é 2.6 g/cm 3 (Menezes et al, 2011;Hoover et al, 1993). Da mesma forma, a figura 8, representa o perfil norte-sul, apresentando um corpo com contraste de densidade negativo no interior, envolto por um corpo de densidade maior, apresentando contraste positivo.…”
Section: Interpretação Dos Dados De Inversão 3dunclassified
“…Esses valores foram obtidos a partir de bibliografias que discutem estes valores para kimberlitos (MENEZES et al, 2011;HOOVER et al, 1993). Nesta modelagem, uma inversão 1D é aplicada, de modo que estes valores puderam ser modificados e ajustados para a área.…”
Section: Modelagem Integradaunclassified
“…Previous works have demonstrated that indicator minerals of kimberlitic intrusions, such as olivine, chromium-diopside, enstatite, serpentine and phlogopite, may have their respective spectral signatures detected by multispectral images (Tessema et al 2012;Nndanduleni and Tessema 2021;Guha et al 2015). Although magnetic and electromagnetic data are commonly used to map kimberlites (Macnae 1995;Pettit 2009;Menezes and La Terra 2011;Kaminski and Oldenburg 2012;Tessema et al 2012;Nndanduleni and Tessema 2021;Matende and Mickus 2021), analysis of airborne gamma-ray spectrometry (AGRS) data can also contribute to reveal the presence of kimberlite-related minerals or to indicate areas where processes related to the formation and alteration of the FIGURE 1. Regional geological map of the study area.…”
Section: Introductionmentioning
confidence: 99%